Antibody-drug conjugates: Principles and clinical results in breast cancer treatment - Loan, Nguyen Phuong; Quan, Duong Hong (Academia Journal of Biology, 2018)
Antibody-drug conjugates (ADCs) are consisted of the combination of highly specific monoclonal antibodies (mAbs) with conventional cytotoxic agents to particular cancer types. The use of mAbs that are specific to tumor cell-surface proteins allows highly selective accumulation of cytotoxic agents as ADCs at the tumor tissue, that is not achievable with conventional cytotoxic agents alone. Designing of effective ADCs for cancer treatment requires identification of an appropriate target, a mAb against the target, potent cytotoxic agents and conjugation of the mAb to cytotoxic agents. Until now, three ADCs including Gemtuzumab ozogamicin, Brentuximab and trastuzumab emtansine have received an FDA approval so far. These three ADCs have shown improved efficacy and safety data compared with standard chemotherapy for the treatment of patients of acute myeloid leukemia, advanced lymphoma and breast cancer, respectively. Moreover, several promising ADCs are now in the latter-phase of clinical testing. Thus, with special focusing on these new anti-cancer drugs, this review briefly describes the principles of ADCs including their structure and mechanism of action, and summarizes their clinical performance in breast cancer. Citation: Nguyen Phuong Loan, Duong Hong Quan, 2017. Antibody-drug conjugates: Principles and clinical results in breast cancer treatment. Tap chi Sinh hoc, 39(4): 489-493. DOI: 10.15625/0866-7160/v39n4.9327. *Corresponding author: quanvspt@gmail.com Received 15 March 2017, accepted 12 December 2017